PENGARUH KEMAMPUAN MEMBACA DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA - Fathia Rosyida (IKIP PGRI Bojonegoro, 2018)
Abstract:Â This research was intended to describe: (1) to what extent does reading ability influence students learning outcomes of Bahasa Indonesia in the second graders of SMAN 2 Bojonegoro; (2) the what extent do students' learning activities in the school influence students learning outcomes of Bahasa Indonesia in the second graders of SMAN 2 Bojonegoro; (3) whether or not reading ability and students learning activities at school simultaneously influence the students learning outcomes of Bahasa Indonesia in the second graders of SMAN 2 Bojonegoro. Based on a simple correlation analysis it was found that the correlation between reading ability and learning outcomes was positive. Regression calculation result between reading ability (X1) and learning outcomes (Y) can be expressed in regression equation Y = 52.116 + 0,338 X1. The result of regression calculation between learning activity (X2) and learning outcomes (Y) can be expressed in regression equation Y = 82.310-0.109 X2. The value of Fo is smaller than Ft (0.452 <3.98) with degree of freedom df1 = 1 and df2 = 78 for 0.05 significance level. Thus, there is no significant relationship between learning activities and learning outcomes. The result of multiple regression calculation showing the relationship between reading ability and learning activity towards students learning outcomes (X1 and X2 on Y) can simultaneously be expressed in regression equation Y = 57.018 + 0.336 X1-0.08385 X2. The value of Fo is higher than Ft (7.201> 3.44) with degree of freedom df1 = 2 and df2 = 77 for 0.05 significance level. Thus, there is a significant corelation between reading ability and learning activities simultaneously towards students learning outcomes.Keywords:Â learning, Bahasa Indonesia, reading ability, learning activities, learning outcomes.Abstrak. Penelitian ini dimaksudkan untuk mendapatkan deskripsi tentang: 1. Sejauhmana kontribusi yang diberikan oleh kemampuan membaca terhadap hasil belajar Bahasa Indonesia Siswa Kelas II SMA Negeri 2 Bojonegoro. 2. Sejauhmana kontribusi yang diberikan oleh aktivitas belajar siswa di sekolah terhadap hasil belajar Bahasa Indonesia Siswa Kelas II SMA Negeri 2 Bojonegoro. 3. Apakah kemampuan membaca dan aktivitas belajar siswa di sekolah memberikan kontribusi secara simultan terhadap hasil belajar Bahasa Indonesia Siswa Kelas II SMA Negeri 2 Bojonegoro. Dari analisis korelasi sederhana ditemukan bahwa korelasi antara kemampuan membaca dengan hasil belajar adalah positif. Hasil perhitungan regresi hubungan antara kemampuan membaca (x1) dengan hasil belajar (Y) dapat dinyatakan dalam persamaan regresi Y= 52,116+ o,338 x1. Adapun hasil perhitungan regresi hubungan antara aktivitas belajar(x2) dengan hasil belajar (Y) dapat dinyatakan dalam persamaan regresi Y=82,310-0,109 x2. Harga Fhitung lebih kecil dari Ftabel (0,452<3,98) dengan derajat kebebasan v1=1 dan v2=78 untuk taraf signifikansi 0,05. Dengan demikian tidak ada hubungan yang signifikan antara aktivitas belajar dengan hasil belajar. Hasil perhitungan regresi ganda yang menunjukkan hubungan antara kemampuan membaca dan aktivitas belajar terhadap hasil belajar (x1 dan v2 atas Y) secara simultan dapat dinyatakan dalam persamaan regresi Y=57,018+0,336 x1-0,08385x2. Harga F hitung lebih besar dari Ftabel (7,201>3,44) dengan derajat kebebasan v1=2 dan v2=77 untuk taraf signifikansi 0,05. Dengan demikian ada hubungan yang signifikan antara kemampuan membaca dan aktivitas belajar secara simultan dengan hasil belajar.Kata kunci: Pembelajaran, Bahasa Indonesia, kemampuan membaca,aktivitas belajar, hasil belajar.